(untitled) (Bangladesh Journal of Pharmacology, 2015)
The purpose of this study was to investigate the anti-diabetic effect of crude Pistacia lentiscus gum (mastic gum) in alloxan-treated diabetic rat model. The crude P. lentiscus (100 mg/kg) showed significant (p<0.001) reduction in blood glucose as compared to control. Liver function test also showed significant changes (p<0.001) as compared to alloxan-treated group. The results of this study showed that crude P. lentiscus gum have considerable efficacy in curing diabetes and have hepatoprotective effect.